On the dialectics of psychoanalytic practice - Morgenthaler, Fritz 1919-1984 (Relational perspectives book series, 2020)
"Fritz Morgenthaler was a crucial figure in the return of psychoanalysis to post-Nazi Central Europe. An inspiring clinician and teacher to the New Left generation of 1968, he was the first European psychoanalyst since Freud to declare that homosexuality is not, indeed never, a pathology, and in Technik, developed revolutionary ideas for transforming clinical technique. On the Dialectics of Psychoanalytic Practice offers the first publication in English of this psychoanalytic, counterculture classic. Those who first picked up Technik encountered it at a historical moment when Marxist psychoanalyst Wilhelm Reich, popular New Left cultural critic Klaus Theweleit, and the texts of the Frankfurt School were already required reading. While not a political text in the same direct way, Morgenthaler's Technik nonetheless shared many of their preoccupations and conclusions about human nature. It was read as technical guidance for psychoanalysts, but also as a manifesto dedicated to the problem of how it might be possible genuinely to live a postfascist, and nonfascist, existence. Morgenthaler was a proto-relationalist, who recombined the traditions of ego and self-psychology as he retained a commitment to drive theory. Here Dagmar Herzog makes his work available to a new generation of analysts, providing essential source material, annotations, and groundbreaking analysis of the continued importance of the work for historians and therapeutic practitioners alike. On the Dialectics of Psychoanalytic Practice will interest practicing clinicians as well as intellectual historians and cultural studies scholars seeking to understand the return of psychoanalysis to post-Nazi Central Europe"--